2009
DOI: 10.1007/s10439-009-9684-3
|View full text |Cite
|
Sign up to set email alerts
|

High Pulsatility Flow Induces Adhesion Molecule and Cytokine mRNA Expression in Distal Pulmonary Artery Endothelial Cells

Abstract: Background-Arterial stiffening or reduced compliance of proximal pulmonary vessels has been shown to be an important predictor of outcomes in patients with pulmonary hypertension. Though current evidence indicates that arterial stiffening modulates flow pulsatility in downstream vessels and is likely related to microvascular damage in organs without extensive distributing arteries, the cellular mechanisms underlying this relationship in the pulmonary circulation are unexplored. Thus, this study was designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 39 publications
4
64
0
Order By: Relevance
“…In our study, the mean flow rates in two flow conditions, high pulsatility flow (PI ϭ 1.7) and low pulsatility or steady flow (PI ϭ 0.2), were always the same and thus the average flow shear (12 dyn/cm 2 ) in the physiological range; the only difference is in the PI, which is modulated by a compliance-adjustment chamber. Our previous study demonstrated that the low pulsatility flows (PI Յ 1) were very different from high pulsatility flows in that they did not elicit endothelial dysfunction such as proinflammatory responses, or they even could protect ECs (23). Additionally, previous studies also showed that it was p-eNOS that was increased by high pulsatile flow compared with low pulsatile flow, whereas the total eNOS was found unchanged by high and low pulsatile flow conditions (56).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In our study, the mean flow rates in two flow conditions, high pulsatility flow (PI ϭ 1.7) and low pulsatility or steady flow (PI ϭ 0.2), were always the same and thus the average flow shear (12 dyn/cm 2 ) in the physiological range; the only difference is in the PI, which is modulated by a compliance-adjustment chamber. Our previous study demonstrated that the low pulsatility flows (PI Յ 1) were very different from high pulsatility flows in that they did not elicit endothelial dysfunction such as proinflammatory responses, or they even could protect ECs (23). Additionally, previous studies also showed that it was p-eNOS that was increased by high pulsatile flow compared with low pulsatile flow, whereas the total eNOS was found unchanged by high and low pulsatile flow conditions (56).…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the design of PI condition in this study, previous studies showed that the mean flow PI in the large elastic PAs (i.e., the first two generations, main PA, left PA, and right PA) ranged from 4.4 to 5.1 in vivo, whereas the PI in the pulmonary capillaries decreased to ϳ1 in vivo (38,43). In addition, our previous study with flows of several PI conditions (1, 1.7, and 2.6) found that only flows with higher PI (1.7 and 2.6) exerted detrimental effects on endothelium when no elastic deformation existed (23). Thus, we have used a PI of 1.7 to represent a high pulsatility flow condition generated by "proximal" artery stiffening.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Several studies compared the impact of steady laminar shear and "realistic" arterial (pulsatile) waveforms on endothelial metabolism and report an increased expression of proinflammatory, proapoptotic, and procoagulant transcripts (25,26) and a reduction of eNOS expression under pulsatile waveforms (27). Himburg et al (28) examined the frequencydependent response of aortic endothelial cells to pulsatile shear stress.…”
Section: Pathophysiology Of Elevated Heart Ratementioning
confidence: 98%
“…This is beginning to change. Recent clinical work has highlighted the importance of PVS in the progression of PH (55, 84, 110), mechanical studies have begun to elucidate the gross vascular changes responsible for stiffening, and existing and novel studies of cellular mechanotransduction suggest PVS may play a role in pulmonary disease pathogenesis (104,105). Many of these concepts have been well-adopted by investigators studying the systemic vascular circuit in health and disease.…”
Section: Introductionmentioning
confidence: 99%